2013
DOI: 10.1007/s12178-013-9178-7
|View full text |Cite
|
Sign up to set email alerts
|

The rheumatoid forefoot

Abstract: Rheumatoid arthritis (RA) manifests itself in a variety of ways, with its effect being seen in around 90 % of sufferers' feet. The foot has been found to be the most common reason for incapacity in patients with RA, with the forefoot the most common area. The foot is second, behind only the hand, as the most common place for manifestation of RA. Pain in the foot is commonly the most debilitating condition, which causes the patient to seek specialist help. As well as pain, foot deformities such as hallux valgus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 57 publications
0
38
1
1
Order By: Relevance
“…However, based on the results of the few studies carried out on this matter [16,17], the impact of the quality of life related to foot health is not as obvious as it appears to be, whereas the results of the present study confirm that people who work at sea present lower scores on the dimensions related to foot pain, foot function, general foot health and social function, than people who work on the ground with normalised reference values. Taking into account these results, it seems necessary to point out the importance of the care and control of the foot in what regards medical and podiatric care in order to prevent the appearance of illnesses and deformities of the foot, this being a key aspect that would allow to improve sea workers' health, quality of life and autonomy.…”
Section: Discussioncontrasting
confidence: 86%
“…However, based on the results of the few studies carried out on this matter [16,17], the impact of the quality of life related to foot health is not as obvious as it appears to be, whereas the results of the present study confirm that people who work at sea present lower scores on the dimensions related to foot pain, foot function, general foot health and social function, than people who work on the ground with normalised reference values. Taking into account these results, it seems necessary to point out the importance of the care and control of the foot in what regards medical and podiatric care in order to prevent the appearance of illnesses and deformities of the foot, this being a key aspect that would allow to improve sea workers' health, quality of life and autonomy.…”
Section: Discussioncontrasting
confidence: 86%
“…Foot problems have been recognized as a public health threat as stated by Nisar and colleagues, who analyzed a sample of 3062 participants with menopause, reporting 861 individuals (28.1%) with muscle and joint pain, which appears to be associated with age, education and menopausal status 4 . In addition, other studies have indicated less satisfaction with the quality of life related to health 19-21 . However, based on the results of the few studies reporting on this subject 22,23 , the impact of the quality of life related to foot health is not as obvious as it appears to be. The results of the present study confirm that menopausal women present with lower scores on the quality-of-life dimensions related to foot health compared to non-menopausal women with normalized reference values.…”
Section: Discussionmentioning
confidence: 99%
“…Joint fusion can be done to stabilize joints that are not easily replaceable such as the ankle, wrist, thumb, and cervical spine. A procedure for soft-tissue release can be done to correct severe contractures around joints causing decreased range of motion; this is an older procedure that is not commonly utilized [45]. Small-joint implant arthroplasty can be done to reduce pain and improve hand function, most commonly in the metacarpophalangeal joints.…”
Section: Surgerymentioning
confidence: 99%